Regulating development banks: a case study of the Brazilian Development Bank (BNDES) (1952-2019) - Martins, Norberto Montani; Torres Filho, Ernani Teixeira (Cadernos do Desenvolvimento, 2023)
This paper analyzes the experience of the Brazilian Development Bank [Banco Nacional de Desenvolvimento Econômico e Social] (BNDES) from 1952 to 2019 to understand how financial regulatory standards influence development banks and their performance as a tool for the socialization of investment and promotion of full employment. We focus on the period after the adoption of Basel standards by Brazilian authorities (1994), presenting and assessing the current regulatory framework that rules BNDES governance, operations, and risk management practices. Our methodology combines a comprehensive review of regulations, relevant data provided by BNDES and the Central Bank of Brazil and semi-structured interviews with BNDES’ staff.